Reform of Civil Servant Pension Benefits Implementation Regulations in the Theory of Law and Development - Sitepu, Dila Kristy Br. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The implementation of Civil Servant Pension Benefits is currently run by PT TASPEN (Persero) since 1987. Payment of Civil Servant Pension Benefits is given monthly for the continuity of old age income as a right and as a reward for the dedication of Civil Servants, as well as the fulfillment of sustainable economic, social and cultural rights and guarantees of a decent life in accordance with duties, responsibilities and obligations. However, with the issuance of Law Number 20 of 2023 concerning the State Civil Apparatus, a new Paradigm has been created regarding the implementation of Civil Servant Pension Benefits. In accordance with Article 22 paragraph (3) and Article 23 of Law Number 20 of 2023 concerning the State Civil Apparatus which states that